Green biosynthesis of silver nanocubes using the leaf extracts from Eucalyptus macrocarpa - Poinern, Gerard; Chapman, Peter; Shah, M.; Fawcett, D. (Global Scientific Publishers 2013, 2013)
In this preliminary study, we present for the first time a facile and environmentally friendly process for the green synthesis of silver nanoparticles using the leaf extract from an indigenous Australia plant Eucalyptus macrocarpa. The synthesis process is performed at room temperature and the leaf extract acts as both reducing agent and stabilising agent. The synthesis process is clean, non-toxic and straightforward and does not need complex processing equipment. The formation of the silver nanoparticles was confirmed by UV-visible spectroscopy, X-ray diffraction, transmission electron microscopy and field emission scanning electron microscopy.